Eosinophilic Esophagitis in Esophageal Atresia: Is It Really a New Disease? - Camilla Pagliara; Elisa Zambaiti; Luca M. Antoniello; Piergiorgio Gamba (MDPI AG, 2022)
Eosinophilic esophagitis (EoE) is a chronic, immune-mediated esophageal disease. Symptoms are related to mucosal eosinophilic-predominant inflammation that leads to esophageal dysfunction. Recent data suggest that esophageal atresia (EA) patients may have an increased incidence of EoE compared to the general population. As EoE symptoms may be confused with EA-related symptoms, they may significantly worsen morbidity in this specific group of patients. We investigated specific characteristics of patients with AE and EoE compared to those with EoE only. We conducted an observational retrospective monocentric study including all patients diagnosed with EoE from 1 January 2010 to 31 December 2021. For each patient, demographic, clinical and histopathological data were collected and then compared between the two cohorts (EA-EoE vs. EoE only). During the study period, 62 patients were included: 17 children were in the follow-up because of EA (18.1% of 94 EA patients screened in that period), while the other 45 presented EoE only. The demographic and clinical features of EA-EoE patients demonstrate a lower prevalence of allergic subjects (23.5% vs. 80%, p < 0.05), a lower age of presentation (3.1 vs. 12.2 years, p < 0.05), non-specific symptoms and a higher resolution rate with PPI therapy (64.7% vs. 17.8%, p < 0.05) compared to EoE-only patients. Our data confirm that EA patients are at high risk for developing EoE. As symptoms may overlap with the EA spectrum, early recognition of EoE may prevent patients from receiving unnecessary invasive therapeutic interventions and from developing complications from untreated EoE.